Artemis of Lapland : Corporate legitimacy and governance of nature in Finnish Lapland - Sokero, Mikael (Helsingin yliopisto, 2016)
The study explores why and how is the legitimacy of the mining project in Sokli, Savukoski municipality in North-Eastern Finland contested. The concept and theory of legitimacy is often neglected in research concerning mining and the concepts of acceptance and social license to operate are found in the mainstream of research. The study discusses the possibilities and challenges the theories and concept of legitimacy in the context of mining. Furthermore the Sokli mine is analyzed in the wider context of the expansion of extractive frontier towards perihpheries. This expansion has been desrcibed to be permitted by a new coalition between the state and private corporations. Moreover the new coalition has been linked to a new development paradigm portrayed as (neo-)extractivism. The literature on extractivism has focused strongly to Global South despite the process’ global character. A case study approach is adapted. The data consists of five semi-structured interviews conducted with locals in Savukoski region. Complimenting the interview data, the analysis is extended to four official documents by stakeholders of the possibly forthcoming mine in Sokli. In the light of a diverse combination of legitimacy theory created in this thesis the legitimacy of the Sokli mine is contested primarily on moral grounds. The mine does not fit into the locals’ conception of how the environment ought to be utilized. The mine also makes the development of traditional livelihoods in the area harder. In sum the locals’ vision of the future of the municipality and their conception of development contradicts with the expansion of the extractive industry. Finnish mining legislation is one of the most important structural permitting condition, which in Savukoski is contested and considered illegitimate. On the other hand the mine is supported mainly for it’s possible tax revenue and because it creates jobs. Employmen moreover is a core argument supporting mining in Finland. There have been controversies between estimations and fulfilled ...